The Countercyclical Capital Buffer and the Composition of Bank Lending - Raphael A. Auer; Steven Ongena (Center for Economic Studies and ifo Institute (CESifo), 2019)
Do macroprudential regulations on residential lending influence commercial lending behavior too? To answer this question, we identify the compositional changes in banks' supply of credit using the variation in their holdings of residential mortgages on which extra capital requirements were uniformly imposed by the countercyclical capital buffer (CCyB) introduced in Switzerland in 2012. We find that the CCyB's introduction led to higher growth in commercial lending although this was unrelated to conditions in regional housing markets. Interest rates and fees charged to the firms concurrently increased. We rationalize these findings in a model featuring both private and firm-specific collateral.
Keywords: E51; E58; E60; G01; G21; G28; 330; macroprudential policy; spillovers; credit; bank capital; systemic risk